Axl inhibitor-mediated reprogramming of the myeloid compartment of the in vitro tumor microenvironment is influenced by prior targeted therapy treatment - Datta, Anisha; Bahlmann, Laura C.; Gong, Diana N.; Tevonian, Erin N.; Lorens, James B.; Lauffenburger, Douglas A. (Frontiers in Immunology, 2025)
Axl, a member of the receptor tyrosine kinase family comprised of Tyro3, Axl, and MerTK, is a promising cancer therapeutic target actively under clinical investigation. Axl is understood to be a dual target in cancer to (1) prevent tumor cell growth and invasion and (2) potentiate anti-tumor immunity. This immunity is characterized by myeloid cell activation and downstream recruitment and activation of anti-tumor T cells. However, the ways by which Axl inhibition promotes myeloid cell activation in the tumor microenvironment are incompletely understood. There is thus a need to understand the effects of Axl inhibition on myeloid cells in the context of the broader tumor microenvironment. Here, we developed a human in vitro model system using primary human monocyte-derived macrophages, primary human monocyte-derived dendritic cells, and Axl-expressing melanoma tumor cells to elucidate the effects of Axl inhibition on the myeloid compartment of the tumor microenvironment. We found that treatment with the Axl-specific small molecule inhibitor bemcentinib yields increased expression of markers of activation in both macrophages and dendritic cells. Interestingly, the addition of dendritic cells to the system appears to dampen macrophage response, suggesting that these cells cooperate to share the burden of the innate immune response. Most importantly, we found that treatment-naïve tumor cells and targeted therapy-treated tumor cells have distinct impacts on macrophage state, and these differences dictate the nature of the immune cell response to Axl inhibition. As a whole, our work highlights the utility of in vitro models in unraveling the complex mechanistic effects of Axl inhibition and establishes a robust model system that can be used in future mechanistic drug studies with the potential to inform clinical trial design.